HOW TO BE A COMPLETE AND UTTER F**K UP 47 1/2 steps to lasting underachievement. - MCDERMOTT, STEVE (PEARSON BUSINESS, 2020)
How to be a Complete and Utter F**k Up is your ultimate ANTI life coach. Be warned: whatever you do, dont do the opposite of what you learn here or else youre in serious danger of making some positive changes and leading a more successful life. How to be a Complete and Utter F**k Up turns the concept of self-improvement on its head. It brings together 47 and a half leading ideas in personal and business development, and oers a total antidote to the motivational, gung-ho, over-enthused tone of all the usual self-improvement guides. Delivered in fast, easily digestible chunks, in a style that makes you laugh while you learn, this book oers tongue-in-cheek advice about what not to do to ensure certain failure in every aspect of your life. From not having any goals, to not getting advice from people youve never met or who are dead, to not taking personal responsibility for your life and results, every idea, strategy, suggestion and story is guaranteed to propel you into the slow lane of total inadequacy and has been tested with thousands of real people. How to be a Complete and Utter F**k Up comes with a warning that you dont think about taking the direct opposite steps to those outlined in the guide, as this could seriously damage your chances of becoming a failure. Behind the humour, though, is good advice and a serious message. And whether you choose to heed the warning or not, its an extremely entertaining read.